The effect of group art therapy on the stress coping ability of Chinese international students in South Korea: using the person-in-the-rain test - Yin, Yue; Ko, Kyung Soon (Frontiers in Psychology, 2024)
Introduction This study aimed to determine the effectiveness of group therapy on the stress coping skills of Chinese students in Korea using a pre-test post-test control group design. Methods Thirty participants were randomly placed into an experimental group (EG; n = 15) and a control group (CG; n = 15). The EG completed eight 120-min sessions of group art therapy. The Person-in-the-Rain (PITR) drawing test was conducted with both groups before and after the EG completed art therapy. Results The test revealed that EG members demonstrated lower stress and significantly higher stress resources and coping abilities than the CG members after the intervention. The group art therapy program improved the EG participants’ ability to deal with stress. Discussion This study’s findings may offer insights useful for determining how best to provide psychological and emotional support to international students who have left their home countries and are continuing their academic journeys abroad.